Peran Humas Palang Merah Indonesia (PMI) Kota Surabaya dalam Menginformasikan Pelayanan Publik kepada Masyarakat - Veiga Octa Dewi Asmara; Ervina Maulidina Hidayati (STIKes Ibnu Sina Ajibarang, 2025)
The Indonesian Red Cross (PMI) is a humanitarian organization that is important in providing public services. This research analyzes the role of PMI Public Relations in conveying information to the public. Through interviews with three sources, namely Headquarters Public Relations, Blood Donor Unit Public Relations, and PMI Clinic Public Relations, and using observation, interview, and documentation methods, this study identified the role of PMI Public Relations as an expert advisor, communication facilitator, problem-solving process facilitator, and technician. Communication. These various roles help PMI Public Relations maintain a positive image of the organization, and strengthen relationships with the community while providing solutions to problems that arise, ultimately increasing public trust in PMI services.